Neurally Adjusted Ventilatory Assist in Very Prematurely Born Infants with Evolving/Established Bronchopulmonary Dysplasia - Shetty, Sandeep; Evans, Katie; Cornuaud, Peter; Kulkarni, Anay; Duffy, Donovan; Greenough, Anne (American Journal of Perinatology Reports, 2021)
Background During neurally adjusted ventilatory assist (NAVA)/noninvasive (NIV) NAVA, a modified nasogastric feeding tube with electrodes monitors the electrical activity of the diaphragm (Edi). The Edi waveform determines the delivered pressure from the ventilator.Objective Our objective was to determine whether NAVA/NIV-NAVA has advantages in infants with evolving/established bronchopulmonary dysplasia (BPD).Methods Each infant who received NAVA/NIV-NAVA and conventional invasive and NIV was matched with two historical controls. Eighteen NAVA/NIV-NAVA infants’ median gestational age, 25.3 (23.6–28.1) weeks, was compared with 36 historical controls’ median gestational age 25.2 (23.1–29.1) weeks.Results Infants on NAVA/NIV-NAVA had lower extubation failure rates (median: 0 [0–2] vs. 1 [0–6] p = 0.002), shorter durations of invasive ventilation (median: 30.5, [1–90] vs. 40.5 [11–199] days, p = 0.046), and total duration of invasive and NIV to the point of discharge to the local hospital (median: 80 [57–140] vs. 103.5 [60–246] days, p = 0.026). The overall length of stay (LOS) was lower in NAVA/NIVNAVA group (111.5 [78–183] vs. 140 [82–266] days, p = 0.019). There were no significant differences in BPD (17/18 [94%] vs. 32/36 [89%] p = 0.511) or home oxygen rates (14/18 [78%] vs. 23/36 [64%] p = 0.305).Conclusion The combination of NAVA/NIV-NAVA compared with conventional invasive and NIV modes may be advantageous for preterm infants with evolving/established BPD.
Keywords: neurally adjusted ventilatory assist; prematurity; neonatal trigger ventilation; length of hospital stay; ventilation days